Proprioceptive Rehabilitation of Upper Limb Dysfunction in Movement Disorders: A Clinical Perspective - Abbruzzese, Giovanni; Trompetto, Carlo; Mori, Laura; Pelosin, Elisa (Frontiers in Human Neuroscience, 2014)
Movement disorders are frequently associated with sensory abnormalities. In particular, proprioceptive deficits have been largely documented in both hypokinetic (Parkinson’s disease) and hyperkinetic conditions (dystonia) suggesting a possible role in their pathophysiology. Proprioceptive feedback is a fundamental component of sensorimotor integration allowing effective planning and execution of voluntary movements. Rehabilitation has become an essential element in the management of patients with movement disorders and there is a strong rationale to include proprioceptive training in rehabilitation protocols focused on mobility problems of the upper limbs. Proprioceptive training is aimed at improving the integration of proprioceptive signals using “task intrinsic” or “augmented feedback”. This perspective article reviews the available evidences on the effects of proprioceptive stimulation in improving upper limb mobility in patients with movement disorders and highlights the emerging innovative approaches targeted to maximizing the benefits of exercise by means of enhanced proprioception.